1996
DOI: 10.1037/0021-9010.81.6.806
|View full text |Cite
|
Sign up to set email alerts
|

A field experiment examining the effects of membership in voting majority and minority subgroups and the ameliorating effects of postdecisional voice.

Abstract: This field study used 80 employees of a data-processing firm to examine the consequences of membership in voting majority and minority subgroups after implementation of a decision and the ability of postdecisional voice to ameliorate the negative consequences of membership in the voting minority. In the absence of postdecisional voice, employees in the minority subgroup perceived the decision process as less fair, were less satisfied with the decision outcome, reported lower levels of task commitment, and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In their meta-analysis, Colquitt, Conlon, Wesson, Porter, and Ng (2001) showed that voice was positively related to the supervisor-rated performance ( r corrected = .17) and organizational citizenship behaviors (OCB; r corrected = .21) of the voicer. In one of the rare organizational justice studies that examined the effect of actual voice behavior (rather than simply the opportunity to voice), Hunton, Price, and Hall (1996) showed that voice, when ignored, resulted in a 41% decrease in output compared to when it was acted upon.…”
Section: Voice and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In their meta-analysis, Colquitt, Conlon, Wesson, Porter, and Ng (2001) showed that voice was positively related to the supervisor-rated performance ( r corrected = .17) and organizational citizenship behaviors (OCB; r corrected = .21) of the voicer. In one of the rare organizational justice studies that examined the effect of actual voice behavior (rather than simply the opportunity to voice), Hunton, Price, and Hall (1996) showed that voice, when ignored, resulted in a 41% decrease in output compared to when it was acted upon.…”
Section: Voice and Outcomesmentioning
confidence: 99%
“…As represented by the dashed line in Figure 1, the majority of the organizational justice literature (with some notable exceptions; e.g., Folger, 1977; Hunton et al, 1996) as well as most of the work in ILR and HRM do not assess whether voice is expressed let alone ignored or acknowledged. This is not to say that the simple opportunity for voice should not have an effect on outcomes; it clearly does.…”
Section: Future Directions For Research On the Effects Of Voicementioning
confidence: 99%
“…Voice is critical to group and organizational outcomes because it is expected to lead to increased learning, better decision making and improved organizational performance (Morrison & Milliken, 2000). For instance, research shows that speaking up is related to higher employee productivity (Hunton et al, 1996) and ratings of performance (see meta-analyses by Ng & Feldman, 2012; Thomas et al, 2010). Although there is less research at the organizational level, some studies suggest that employee voice is related to lower turnover and is important because it allows organizational leadership to identity important issues (see Bashshur & Oc, 2015, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the potential risk of voice itself, leaders’ response to/feedback on employees’ voice (eg, leader voice endorsement) is a key factor that alters the impact of voice for individuals. Hunton et al 15 revealed that when voice is ignored, it would result in a 41% reduction in output in comparison to when it was endorsed.…”
Section: Introductionmentioning
confidence: 99%